2013
DOI: 10.1007/s10096-013-1831-y
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 and GSTT1 genetic polymorphisms and risk of anti-tuberculosis drug-induced hepatotoxicity: an updated meta-analysis

Abstract: The results of studies investigating the associations between GSTM1 and GSTT1 polymorphisms and anti-tuberculosis drug-induced hepatotoxicity (ADIH) risk exhibit much controversy. Therefore, a meta-analysis was performed in order to examine the associations between GST variants and ADIH risk. A total of 451 relevant studies were identified through the digital medical databases Medline, Embase, and CBM published up to October 2012. Thirteen individual case-control studies were eventually recruited for GSTM1 nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 41 publications
6
49
0
1
Order By: Relevance
“…A recent large-scale meta-analysis of GST variants, which included 13 and 12 case-control studies for the GSTM1 and GSTT1 null genotypes, respectively (approximately 900 cases and 1900 controls for each gene), found evidence that the null genotype of GSTM1 , but not GSTT1 , was associated with marginally increased susceptibility to ATT-DILI [114], which was consistent with the previous meta-analyses [111, 112]. …”
Section: Meta-analyses Of Nat2 Cyp2e1 Gstm1 and Gstt1 Genotypessupporting
confidence: 80%
“…A recent large-scale meta-analysis of GST variants, which included 13 and 12 case-control studies for the GSTM1 and GSTT1 null genotypes, respectively (approximately 900 cases and 1900 controls for each gene), found evidence that the null genotype of GSTM1 , but not GSTT1 , was associated with marginally increased susceptibility to ATT-DILI [114], which was consistent with the previous meta-analyses [111, 112]. …”
Section: Meta-analyses Of Nat2 Cyp2e1 Gstm1 and Gstt1 Genotypessupporting
confidence: 80%
“…A clinical study in an Indian patient population indicated that GSTM1 and GSTT1 null genotypes are associated with high rates of AT-DILI [64]. A meta-analysis that considered 451 relevant studies before 2013 found a strong association between certain GSTM1 genotypes and an elevated risk of AT-DILI after combined treatment with isoniazid and rifampicin [65]. Association of GSTT1 null genotypes with the risk of AT-DILI only exists in some East Asian populations [65].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…A meta-analysis that considered 451 relevant studies before 2013 found a strong association between certain GSTM1 genotypes and an elevated risk of AT-DILI after combined treatment with isoniazid and rifampicin [65]. Association of GSTT1 null genotypes with the risk of AT-DILI only exists in some East Asian populations [65]. Another meta-analysis-based study of 20 published association reports collectively conducted on over 5000 subjects also revealed the presence of a significant association between GSTM1 genotypes and risk of AT-DILI, but no association with GSTT1 genotypes [66].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…A p value less than 0.1 (I 2 [ 50 %) indicated statistical significant heterogeneity existed among the studies, and random-effects model was used to calculate ORs with corresponding 95 % CIs. In contrast, p values greater than 0.1 (I 2 \ 50 %) indicated no statistical significant heterogeneity existed among studies, and the fixed-effects model was used to calculate ORs with corresponding 95 % CIs [16]. We first calculated the combined ORs using the fixed-effects model.…”
Section: Discussionmentioning
confidence: 99%